Optical ammonia gas sensor of poly(3,4-polyethylenedioxythiophene), polyaniline and polypyrrole: a comparative study - Ismail, Abdul Hadi; Mohd Yahya, Nor Akmar; Yaacob, Mohd Hanif; Mahdi, Mohd Adzir; Sulaiman, Yusran (Elsevier, 2020)
In this work, the optical sensing performance of three different types of conducting polymers, polyaniline (PANI), poly(3,4-ethylenedioxythiophene) (PEDOT) and polypyrrole (PPy) towards ammonia (NH3) gas has been evaluated. The sensing analyses of the respective conducting polymers were measured in the optimised wavelength ranges that manifest absorbance response upon exposure to NH3 gas. Based on the dynamic response where the respective conducting polymers were exposed to NH3 gas within the concentration range of 0.0625 % to 1 %, PEDOT exhibited the highest sensitivity (9.03/%) towards NH3 gas comparing to PANI and PPy with the detection limit of 2.73 ppm, which is in agreement with their respective conductivity trends.